Entrepreneurial Behavior Based On Religious Values And Performance: The Mediating Role Of The Need For Achievement And Internal Locus Of Control - Iskandar Iskandar; Iyan Setiawan; Agie Hanggara; Sri Mulyati (UNIVED Press, 2025)
This study aims to determine the direct and indirect effects of entrepreneurial behavior based on religious values, achievement drive, and internal locus of control on business performance. Data collection utilizes questionnaires with a purposive sampling technique totaling 100 MSME entrepreneurs (Micro, Small, and Medium Enterprises) in Kuningan Regency. Data analysis used Path Analysis with SPSS statistical software to determine the variables’ direct and indirect effects. According to the findings of the study, 1) Entrepreneurial behavior based on religious values has a significant and positive influence on business performance. 2) need for achievement mediates the influence of entrepreneurial behavior based on religious values on business performance. 3) internal locus of control does not mediate the influence of entrepreneurial behavior based on religious values on business performance. The main finding of this study is that the need for achievement has a greater influence on the business performance of MSMEs (Micro, Small, and Medium Enterprises) both directly and indirectly. The results of the study show that the need for achievement has a greater direct and indirect influence on business performance indicating that the need for achievement reflects strong personality characteristics to become a successful entrepreneur.